Viaje a un mito de autor a través de los géneros en El muerto y ser feliz (Javier Rebollo 2012) (Periphērica, 2020)
At a time when the concept of auteur cinema is being deeply questioned, the cinematographic work of Spanish director Javier Rebollo (1969-) can be understood as a sample of formal characteristics and experimental narratives leading to a reaffirmation of director as an auteur. In Rebollo’s third film, El muerto y ser feliz (The Dead Man and Being Happy 2012), Santos, a dying hitman, goes on a journey from Buenos Aires to Northern Argentina that progressively acquires a symbolic meaning, as it is a journey from civilization to nature, from life to death, and, ultimately, from history to myth. The physical decline of Santos and his overcoming of physical death–and of linear time–through his transformation in myth, is parallel to a deconstruction of traditional cinematic language in the movie. Through a meta-reflective articulation of the road movie genre and through the distancing effect caused by the existence of two narrators who, competing with each other, simultaneously construct and deconstruct Santos’ story with their ironic and polysemic words, Rebollo attempts to reaffirm his position as a director-auteur, as the sole creator of an auteur myth (“mito de autor”) versus the traditional myth, oral and collective by nature.